Gracing of Sociotechnical Virtues - Graves, Mark (2025)
Can AI be virtuous? The answer depends upon one’s definitions of virtue and AI. A meaningful threshold is to consider virtue theologically, as something that could receive grace, and to situate AI sociotechnically, recognizing mutual influences between technology and society. Extending the human dispositions and ends underlying virtue to include computational dispositions and norms facilitates examining sociotechnical virtue. I argue that even if virtue requires grace for full realization, AI can still be virtuous in its sociotechnical context. I illustrate this through the gracing of sociotechnical virtue from Protestant (John Wesley), Roman Catholic (Karl Rahner), and Orthodox Christian (Irenaeus) perspectives.
Keywords: Virtue Ethics; sociotechnical systems; nature and grace; Habitus; Christian Ethics; Artificial Intelligence